TRAINING AND MAKING PLOT OF SALINE LAND MANAGEMENT TECHNOLOGY TO INCREASE RICE PRODUCTION - Syamsul Bahri; Muhammad Syahril; Dolly Sojuangan (Global Science Society, 2021)
Soil salinity due to the accumulation of NaCl salts is the cause of the largest land damage in the world. The build-up of NaCL salts on the ground can be caused by sea water intrusion. As a result, many saline lands are scattered around the Indonesian lotus line, including Langsa city, especially Sungai Lueng Village. Soil salinity can disrupt plant growth so that production is low, including rice. The results showed that the farmers planted Ciherang varieties with productivity ranging from 4-5 tonnes / ha. Precise handling through application of technology to reduce the effects of salinity. The use of Na-metal washing technology as a source of toxicity for rice plants can be done by utilizing rainwater whose effectiveness is increased by adding gypsum. In addition to Na leaching, the use of Banyuasin salinity tolerant varieties will also be carried out. Through this PKM, it is hoped that the saline land in Langsa City can be utilized optimally and specifically rice production in Sungai Lueng village can increase to support food sovereignty.